2012
DOI: 10.1016/j.polymer.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of photo-induced crosslinking of thymine polymers using FT-IR spectroscopy and chemometric analysis

Abstract: Please cite this article as: Bortolato SA, Thomas KE, McDonough K, Gurney RW, Martino DM, Evaluation of photo-induced crosslinking of thymine polymers using FT-IR spectroscopy and chemometric analysis, Polymer (2012), doi: 10.1016/j.polymer.2012.09.007. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 42 publications
(41 reference statements)
6
35
0
Order By: Relevance
“…Making use of these results and Equation (2) (Section 2), it is possible to identify the kinetics profiles of the species involved in the curing reaction ( Figure 5). Interestingly, the kinetics profiles are in agreement with reported results for VBT-VBA copolymers (16,18), suggesting that the curing process is only VBT-dependent. On the other hand, for each copolymer composition, the VPS species remains constant throughout the entire cross-linking reaction, while as the concentration of the VPS interferent augments, the chemometric resolution gets worse ( Figure 5(e)).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Making use of these results and Equation (2) (Section 2), it is possible to identify the kinetics profiles of the species involved in the curing reaction ( Figure 5). Interestingly, the kinetics profiles are in agreement with reported results for VBT-VBA copolymers (16,18), suggesting that the curing process is only VBT-dependent. On the other hand, for each copolymer composition, the VPS species remains constant throughout the entire cross-linking reaction, while as the concentration of the VPS interferent augments, the chemometric resolution gets worse ( Figure 5(e)).…”
Section: Resultssupporting
confidence: 90%
“…Regarding the spectral features of the excitation and emission profiles assigned to VBT (blue line in Figure 6(c)), reported data for thymine fluorescence (20) indicate a comparable emission maximum at 400 nm (λ exc = 295 nm), even if no quantitative evaluation of such similarity is possible. Finally, the refolded spectral profiles designed for the species generated in the curing reaction are in agreement with previously reported data (16,18), allowing us to make a suggestion of the species involved in the curing process (see Scheme 1).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Besides, it can be found that the characteristics peak at 1385 cm -1 assigned to -CH 3 stretching vibration in amino resin also decreased due to its reaction with epoxide group and hydroxyl group. Surprisingly, the peaks at 3447 cm -1 assigned to -OH stretching vibration increased over time in DEN/HMMM/EMI-24 system, which was due to the higher reaction activity of epoxide than that of hydroxyl, and the produced -OH was more than the consumed -OH, and these -OH increased the polar of cured polymer [34][35][36][37]. The relative high polarity of -OH resulted in high dielectric constant and water absorption, and the results were consistent with our previous works [15].…”
Section: Isothermal Ftir Analysismentioning
confidence: 96%